A formação de "bons cristãos e virtuosos cidadãos": atuação dos Irmãos Maristas em Passo Fundo (1929-1950) - Vanelli, Natália Carla (2021)
The dissertation analyzes the performance of the Congregation of the Marist Brothers in the City of Passo Fundo, through the Marist College Nossa Senhora da Conceição during the years 1929 to 1950. The Congregation of the Marist Brothers emerged in France in 1816 with the aim of spreading the Catholic faith in formative environments. Its members find in education a way to accomplish this task, through evangelization. With its consolidation in Europe, evangelization was expanded, also to other continents. In Brazil, during the transition period from the Brazilian Empire to the Republic (1899), the country had a very low number of dioceses, each with few priests. Faced with the context of state laicization, the Brazilian ecclesiastical authorities are committed to strengthening a more solid and profound Catholicism in the country, with the educational field being a strategic space for the new objectives established by the Catholic Church. In this sense, there is an invitation to the Congregation of the Marist Brothers to assume the educational role in Brazilian municipalities. The teaching method adopted by the brothers was a confessional model (schools that educated in a male boarding school and boarding school model (until 1960), each of them having differences in their methodologies, but similar proposals and objectives) where, in addition to trying to carry out the standardization and social adequacy of their students, catechized and induced the Catholic faith. The analysis will approach the teaching institute as a Total Institution as a guiding category (due to the theoretical contribution of Goffman, Benelli and Foucault), focusing on the boarding school model offered to students at Colégio Marista Nossa Senhora da Conceição in Passo Fundo. by the institution. The presence of this institution and its importance for the construction of the personality and character of the students are pointed out, as well as its strict methods of implementing the discipline, conceptualizing Silvio José Benelli and Michel Foucault, in order to standardize and prepare its internal public for the society of the period. Based on an analysis of the institutional documentation of the Marist Congregation, images, sources of periodicals and other sources, the work highlights the Marist investment in the formation of “good citizens” and “good Catholics” and the efforts for disciplining, catechizing, time management and inmates' activities in a controlled environment.